Rationale and design of a multicenter randomized study for evaluating vascular function under uric acid control using the xanthine oxidase inhibitor, febuxostat: the PRIZE study. Issue 1 (December 2016) - Oyama, Jun-ichi; Tanaka, Atsushi; Sato, Yasunori; Tomiyama, Hirofumi; Sata, Masataka; Ishizu, Tomoko; Taguchi, Isao; Kuroyanagi, Takanori; Teragawa, Hiroki; Ishizaka, Nobukazu; Kanzaki, Yumiko; Ohishi, Mitsuru; et al.
Abstract Background Xanthine oxidase inhibitors are anti-hyperuricemic drugs that decrease serum uric acid levels by inhibiting its synthesis. Xanthine oxidase is also recognized as a pivotal enzyme in the production of oxidative stress. Excess oxidative stress induces endothelial dysfunction and inflammatory reactions in vascular systems, leading to atherosclerosis. Many experimental studies have suggested that xanthine oxidase inhibitors have anti-atherosclerotic effects by decreasing in vitro and in vivo oxidative stress. However, there is only limited evidence on the clinical implications of xanthine oxidase inhibitors on atherosclerotic cardiovascular disease in patients with hyperuricemia. We designed the PRIZE study to evaluate the effects of febuxostat on a surrogate marker of cardiovascular disease risk, ultrasonography-based intima-media thickness of the carotid artery in patients with hyperuricemia. Methods The study is a multicenter, prospective, randomized, open-label and blinded-endpoint evaluation (PROBE) design. A total of 500 patients with asymptomatic hyperuricemia (uric acid >7.0 mg/dL) and carotid intima-media thickness ≥1.1 mm will be randomized centrally to receive either febuxostat (10–60 mg/day) or non-pharmacological treatment. Randomization is carried out using the dynamic allocation method stratified according to age (<65, ≥65 year), gender, presence or absence of diabetes mellitus, serum uric acid (<8.0, ≥8.0 mg/dL), and carotid intima-media thickness (<1.3, ≥1.3 mm). In addition to administering the study drug, we will also direct lifestyle modification in all participants, including advice on control of body weight, sleep, exercise and healthy diet. Carotid intima-media thickness will be evaluated using ultrasonography performed by skilled technicians at a central laboratory. Follow-up will be continued for 24 months. The primary endpoint is percentage change in mean intima-media thickness of the common carotid artery 24 months after baseline, measured by carotid ultrasound imaging. Conclusions PRIZE will be the first study to provide important data on the effects of febuxostat on atherosclerosis in patients with asymptomatic hyperuricemia. Trial Registration Unique trial Number, UMIN000012911 (https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr.cgi?function=brows&action=brows&type=summary&recptno=R000015081&language=E )